Determinants of Maize Production Income in Western Uganda. - Midamba, Dick Chune (East African Journal of Agriculture and Biotechnology, 2022)
Many smallholder farmers produce maize for both consumption and income purposes. Despite the role played by maize, its income production is low, especially in developing countries. In order to formulate policies targeting maize productivity, it was necessary to have knowledge of the determinants of maize production income. As such, this study aimed at determining the level of income and its determinants from maize farmers. Consequently, data was collected from 220 maize farmers using structured questionnaires. The ordinary least squares model was used to determine the determinants. The results showed that the farmers earned a mean of 372,207 Ugandan shillings (105.18 USD) from maize production. Accordingly, farm size, access to credit and household size had a significant positive influence on income from maize production, while gender (female) of the household heads had a significant negative relationship with income from maize production. It is based on these results that this study recommended that the government should offer training programs targeting female-headed households. These trainings should incorporate farm production as well as marketing. Additionally, farmers should be encouraged to access various sources of agricultural credit including financial institutions that offer agricultural loans at low-interest rates.
Keywords: Maize Production Income; Determinants; Farmers